THE GROWTH OF ACCOUNTING INSTRUCTION SINCE 1900. - Allen, C. E. (The Accounting Review, 1927)
Abstract The purpose of this paper is to show the growth of instruction in accounting in the U.S. universities and colleges from 1900 to the present, as of June 1927. The interest in accounting has also grown rapidly in secondary schools, normal schools, and foreign schools in this same period, but the scope of this study is restricted to the U.S. universities and colleges. The year 1900 was selected as a starting point because instruction in accounting prior to that time was not very important. In fact, even during the first few years following 1900 there was not much development in accounting instruction in the universities; and in such work as was given the art and science of bookkeeping were emphasized rather than the fundamental principles of accounting. In order to determine the extent of this growth a study was made of the courses in accounting as shown by the catalogues of forty two of the leading universities and colleges. In this study the catalogues were carefully examined for each year from 1900 to 1926, inclusive. In addition, in order to determine definitely the growth in the number of schools giving courses in accounting, the catalogues of seventy-five additional universities and colleges were studied for the year 1900, 101 for 1910, 303 for 1916, and 575 for 1926.